Incidence and treatment outcome of oral lichen planus in Southeast Serbia in a 10-year period (1997-2007) - Kesić Ljiljana; Obradović Radmila; Mihailović Dragan; Radičević Goran; Stanković Saša; Todorović Kosta (Vojnosanitetski Pregled)
Background/Aim. Lichen planus is a chronic, immunologic, mucocutaneous disease with a wide range of clinical manifestations. The aim of this retrospective study was to evaluate the most common forms of oral lichen planus (OLP) and its symptoms and to describe treatment responses in patients during 10-year period. Methods. The study was conduced on 163 OLP patients who came in the Department of Oral medicine and Periodontology between 1997 and September 2007. Each case was classified into one of four clinical subtypes: reticular, atrophic, erosive-ulcerative, bullous. Results. There was no significant difference in patients age. Women were found to be significantly more likely to have OLP (p < 0.001). Corticosteroids were effective in reducing symptoms, erythema and healing ulcers. Improvement was shown over a long term in 61.35% patients. Over the long term 38.65% patients maintained the same type of OLP or it became a more severe type. Two patients (1.22%) developed oral carcinoma during the follow-up period. Conclusion. The response of patients with erosive OLP to a short course of systemic corticosteroids often was quite remarkable. However, symptoms and signs tended to recur after this treatment. Periodic examinations, patient education, medical treatment, monitoring of side-effects as well as follow-up biopsies are necessary for management of OLP patients.